The Implementation of Quipper Campus in English Language Assessment: A Qualitative Case Study - Yuniar, Rendhi Fatrisna (Proceeding of International Conference on Islamic Education (ICIED); Vol 9 No 1 (2024): Proceeding of International Conference on Islamic Education (ICIED)DO - 10.18860/icied.v9i1.3159, 2024)
Technological advancements in education are encouraging the next generation to enhance skills in computer-based learning. Educational media, such as Quipper Campus, have increasingly adopted online platforms to make learning more effective and efficient. This study explores teachers and students perceptions of using Quipper Campus in teaching and learning process, especially for English class. This research also focuses on the implementation of Quipper Campus on assessments aspect and investigates how the platform can facilitate effective and efficient assessment processes. The research was conducted at university level in Indonesia, involving ten English lecturers and thirty students which are selected through purposive sampling. A qualitative case study approach was employed, using interviews, observations, and documentation as data collection instruments. Data analysis followed Miles and Huberman’s approach, consisting of data reduction, data presentation, and conclusion drawing. The findings indicate that Quipper Campus supports seven of the eleven types of assessments defined in Permendikbud No. 66 of 2013 on educational standards, including self-assessment, authentic assessment, portfolio-based assessment, and daily tests. Moreover, Quipper Campus’s adaptability is highlighted as it supports multiple curriculum standards, allowing teachers to provide relevant and tailored content. However, mid-semester and end-semester tests are not implemented on the platform due to Quipper lacks comprehensive security features to prevent cheating during exams, such as automatic proctoring, plagiarism detection, or browser locking.